A Compensatory Model of Risk and Resilience Applied to Adolescent Sexual Orientation Disparities in Nonsuicidal Self-Injury and Suicide Attempts. - Reisner, Sari L; Biello, Katie; Perry, Nicholas S; Gamarel, Kristi E; Mimiaga, Matthew J (The American journal of orthopsychiatry, 2014)
This study investigated and applied a compensatory model of risk and resilience to differences in past-year nonsuicidal self-injury (NSSI) and suicide attempts by sexual orientation using representative data from the 2007 Massachusetts Youth Risk Behavior Survey (n = 3,131). Self-identified lesbian, gay, bisexual, and questioning (LGBQ) adolescents comprised 7% of the sample, but accounted for 67% of NSSI and 80% of suicide attempts. Compared with heterosexuals, LGBQ adolescents had an increased odds of NSSI (adjusted Odds Ratio (aOR) = 2.76; 95% Confidence Interval (CI) [2.00, 3.81] and suicide attempts (aOR = 2.73; 95% CI [1.47, 5.08]. NSSI was highly associated with suicidality (aOR = 10.87; 95% CI [6.17, 19.18]. Family support was independently associated with a decreased odds of both NSSI (aOR = 0.56; 95% CI [0.35, 0.89] and suicidality (aOR = 0.48; 95% CI [0.29, 0.79] supporting a compensatory model of resilience. Screening and preventive interventions for LGBQ adolescents are warranted, including at the family level. Sexual orientation should be included as a standard demographic to monitor health disparities. (PsycINFO Database Record (c) 2014 APA, all rights reserved).